2004
DOI: 10.1634/stemcells.22-1-12
|View full text |Cite
|
Sign up to set email alerts
|

Limited Contribution of Circulating Cells to the Development and Maintenance of Nonhematopoietic Bovine Tissues

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 73 publications
0
13
0
1
Order By: Relevance
“…We observed changes in the expression of genes which regulate the renewal of hematopoietic stem cells (HSCs), e.g., HOXB4, MLL5, TAC1, and MYB. HSCs are particularly important in the context of their penetration into the mammary gland and their potential effect on glandular development (Niku et al 2004). HOXB4 (showing up-regulated expression in this study) activates Myc transcription factor, which also showed a higher expression.…”
Section: Discussionmentioning
confidence: 99%
“…We observed changes in the expression of genes which regulate the renewal of hematopoietic stem cells (HSCs), e.g., HOXB4, MLL5, TAC1, and MYB. HSCs are particularly important in the context of their penetration into the mammary gland and their potential effect on glandular development (Niku et al 2004). HOXB4 (showing up-regulated expression in this study) activates Myc transcription factor, which also showed a higher expression.…”
Section: Discussionmentioning
confidence: 99%
“…To date, Friedenstein's procedure is considered a standard protocol to isolate bone marrow (BM) MSCs (4,14,15). Isolation and phenotypic characterization of MSCs have been demonstrated in several vertebrate species, including human (6,12,16), murine (4,5,15), lapine (17), canine (18), ovine (19), avian (20), porcine (21), equine (22), and bovine (23). However, MSC colonies isolated by adherence to the plastic culture plate are heterogeneous, likely containing osteoblasts and/or osteoprogenitor cells, fat cells, fibroblasts, reticular cells, macrophages, endothelial cells, and a fraction of blood cells and hematopoietic stem cells (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…We have always assumed that these are analogous in different taxa, but perhaps this is an error to make such an assumption. Niku et al ( 2004 ) showed that among the hematopoietic precursors are some remarkably multipotent cells that are irregularly distributed throughout the body and that become especially prominent in granulation tissue. From the same laboratory comes evidence of the variable percentage of B-and T-cells.…”
Section: Chimerism Mosaicismmentioning
confidence: 99%